Practice of Lasallian values and leadership skills of Lay Administrators in Lasallian Educational Institutions - Guia, Riff Raymond; Legaspi Jr, Carlos Eduardo (Technium Social Sciences Journal, 2023)
Core values will create an impact on the performance of members. This studyisanchored on values-based leadership and inspired by Lasallian spirituality. Lasalliancorevalues are faith, zeal for service, and communion in mission. On the other hand, the Lasallianleadership skills in this study are derived from the inspiring metaphors of the founder St. JohnBaptist de La Salle, and the ancient writing ideas of Br. Agathon FSC. With these perspectives, the study was conducted among the Lasallian lay administrators in Bacolod City. Thisresearch also determined the relationship between the two variables. A validated questionnairewas created by the author and 16 members of the Lasallian community. The questionnairewas given to the 81 lay administrators from the two Lasallian institutions within BacolodCity, Negros Occidental, Philippines. The results showed that their practices of Lasalliancorevalues and leadership skills are to a very great extent, yet there is a clear discrepancy inthenumber of years serving the institution. The study also presented a clearer viewof the ideathat there is a significant relationship between the two. The output recommended the creationor enhancement of the Lasallian Adult Formation program matrix.